Are tree seed systems for forest landscape restoration fit for purpose? An analysis of four Asian countries - Bosshard, Ennia; Jalonen, Riina; Kanchanarak, Tania; Yuskianti, Vivi; Tolentino, Enrique L.; Warrier, Rekha R.; Krishnan, Smitha; Dzulkifli, Dzaeman; Thomas, Evert; Atkinson, Rachel; Kettle, Christopher J. (MDPI, 2021)
High-quality, suitably adapted tree seed at volume is a key component for the implementation and long-term success of forest landscape restoration (FLR). We analysed the tree seed systems in four Asian countries—the Philippines, Indonesia, Malaysia and India—which have committed to restore in total over 47.5 million hectares of degraded lands by 2030. We assessed the national seed systems using an established indicator framework, literature review and expert surveys and interviews. Additionally, we surveyed 61 FLR practitioners about their challenges in acquiring seed to understand how the strengths and weaknesses identified at the national level were reflected in FLR projects on the ground. Identified key constraints common to the studied countries are (i) a mismatch between the growing demand for priority native species and the limited seed supply in terms of quantity and quality, (ii) lack of effective quality control for seed of native species and (iii) lack of information about the effects of climate change on native species to guide species selection and seed sourcing and to improve the resilience of restored ecosystems. We discuss options to strengthen seed systems for native tree species both in terms of quality and volume to enable them to effectively respond to the national FLR commitments and make recommendations on promising technical solutions.